Intersection of Ecology and Literature in Kire’s when the River Sleeps - P.S Luireiphy, (International Journal of Scientific Research in Science and Technology, 2024)
This paper explores the intersection of ecology and literature in Easterine Kire’s When the River Sleeps by analyzing how Kire’s narrative brings forward an ecological perspective by intertwining ecological consciousness with storytelling. Easterine Kire uses storytelling to reveal the intrinsic connection between the indigenous Naga people and their environment, depicting nature as living, sacred presence with which humans interact respectfully and reciprocally. Through literature, Kire advocates for a form of ecological guardianship rooted in cultural heritage, engaging readers in a broader dialogue about sustainability, respect for the natural world, and the urgent need to protect these ecosystems and the knowledge they hold. She uses literature to convey deep ecological knowledge, values, and cultural beliefs to readers, fostering a profound awareness of the natural world.
Keywords: ecology; storytelling; advocates; indigenous; sustainability; values